2018
DOI: 10.1016/j.amsu.2018.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of attitude and knowledge on intention to breastfeed: Can mHealth based education influence decision to breastfeed exclusively?

Abstract: BackgroundExclusive breastfeeding has been endorsed as the healthiest feeding choice for newborns. This study aims to assess impact of expecting mothers’ knowledge and attitude toward intention to breastfeed exclusively. Utilizing mobile health (mHealth) as educational tool can offer a widely distributed and affordable platform to promote exclusive breastfeeding.Research aims and questionsThis study aims to assess impact of expecting mothers’ knowledge, attitude and beliefs on decision to breastfeed exclusivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 17 publications
2
43
1
Order By: Relevance
“…We do not have similar previous studies for comparisons, as this study is, to our knowledge, the first study of its kind in the Dominican Republic. However, other studies have assessed the feasibility and acceptability of mHealth apps aimed at improving breastfeeding in other countries [ 27 - 30 ]. For example, in Saudi Arabia, more mothers expressed their intention to practice EBF after receiving mHealth-based education about EBF and early breastfeeding initiation [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We do not have similar previous studies for comparisons, as this study is, to our knowledge, the first study of its kind in the Dominican Republic. However, other studies have assessed the feasibility and acceptability of mHealth apps aimed at improving breastfeeding in other countries [ 27 - 30 ]. For example, in Saudi Arabia, more mothers expressed their intention to practice EBF after receiving mHealth-based education about EBF and early breastfeeding initiation [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have assessed the feasibility and acceptability of mHealth apps aimed at improving breastfeeding in other countries [ 27 - 30 ]. For example, in Saudi Arabia, more mothers expressed their intention to practice EBF after receiving mHealth-based education about EBF and early breastfeeding initiation [ 27 ]. An Australian study reported high ratings for an evidence-based breastfeeding app designed to provide men with social support and information to enhance the help they can offer their breastfeeding partners [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this type of examination is lacking in nursing research which, while acknowledging the influence of system-level factors such as structural racism, social and cultural norms, and lack of public policy to support breastfeeding, has largely focused on individual characteristics and behaviors when studying breastfeeding interventions (Johnson, Kirk, Rosenblum, et al, 2015;Reno et al, 2018). These individual characteristics include maternal attitude (Alnasser et al, 2018;Shepherd, Walbey, & Lovell, 2017), self-efficacy (Henshaw, Fried, Siskind, Newhouse, & Cooper, 2015;McQueen, Dennis, Stremler, & Norman, 2011), and personality (Brown, 2014).…”
Section: Current Re S E Arch Find Ing Smentioning
confidence: 99%
“…Surgeon General issued a “Call to Action to Support Breastfeeding,” bringing attention to the fact that, despite knowledge about the benefits of breastfeeding, the United States continues to fall short of national goals and maintains pervasive disparities in breastfeeding outcomes (Anstey, ; US Department of Health & Human Services, ). Current nursing research examining breastfeeding has had considerable focus on these disparities, but concentrates heavily on individual factors associated with breastfeeding, such as maternal attitude or partner support (Alnasser et al, ; Bhairo & Elliott, ; Rempel, Rempel, & Moore, ). This focus on individual‐level interventions, while an important aspect of improving breastfeeding rates, fails to acknowledge systemic and structural barriers to breastfeeding, such as lack of paid family leave, failure to regulate formula advertising, and the systemic racism that influences cultural norms and access to unbiased care (Johnson, Kirk, Rosenblum, & Muzik, ; Jones, Power, Queenan, & Schulkin, ; Reno, Barnhart, & Gabbe, ).…”
Section: Introductionmentioning
confidence: 99%